Synaptic GABAergic transmission in the central amygdala (CeA) of rats depends on slice preparation and recording conditions. Issue 19 (6th October 2019) - Avegno, Elizabeth M.; Middleton, Jason W.; Gilpin, Nicholas W.
Abstract: The central nucleus of the amygdala (CeA) is a primarily GABAergic brain region implicated in stress and addictive disorders. Using in vitro slice electrophysiology, many studies measure GABAergic neurotransmission to evaluate the impact of experimental manipulations on inhibitory tone in the CeA, as a measure of alterations in CeA activity and function. In a recent study, we reported spontaneous inhibitory postsynaptic current (sIPSC) frequencies higher than those typically reported in CeA neurons in the literature, despite utilizing similar recording protocols and internal recording solutions. The purpose of this study was to systematically evaluate two common methods of slice preparation, an NMDG‐based aCSF perfusion method and an ice‐cold sucrose solution, as well as the use of an in‐line heater to control recording temperature, on measures of intrinsic excitability and spontaneous inhibitory neurotransmission in CeA neurons. We report that both slice preparation and recording conditions significantly impact spontaneous GABAergic transmission in CeA neurons, and that recording temperature, but not slicing solution, alters measures of intrinsic excitability in CeA neurons. Bath application of corticotropin‐releasing factor (CRF) increased sIPSC frequency under all conditions, but the magnitude of this effect was significantly different across recording conditions that elicited different baseline GABAergic transmission. Furthermore, CRF effects on synaptic transmission differed according to data reporting methods (i.e., raw vs. normalized data), which is important to consider in relation to baseline synaptic transmission values. These studies highlight the impact of experimental conditions and data reporting methods on neuronal excitability and synaptic transmission in the CeA. Abstract : The central nucleus of the amygdala (CeA) has a demonstrated role in fear, anxiety, and addiction. Modulation of CeA neuronal activity via an extensive inhibitory network is often studied using in vitro electrophysiological studies. However, methodological approaches in these experiments are not always consistent. We present a systematic comparison of slicing and recording conditions for in vitro experiments and propose optimal conditions for measurement of inhibitory transmission in the CeA.